THE EFFECT OF TEAM CHRACTERISTICS, ORGANIZATIONAL JUSTICE, AND WORK ETHIC ON TEACHER JOB PERFORMANCE OF STATE PRIMARY SCHOOL AT EAST JAKARTA - Mansur Hakim; Mukhneri Mukhtar; Thamrin Abdullah (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The objective of this research is to study the effect of team chracteristics, organizational justice, and work ethic on teacher job performance of state primary school at East Jakarta. The research method is quantitative with survey. The samples of this research were 209teachers selected randomly. The data were analyzed by using descriptive statistics and path analysis. The results of the research can be concluded that: team chracteristics, organizational justice, and work ethic had a direct effect on teacher job performance;team chracteristics had a direct effect on teacher work ethic; and team chracteristics had a direct effect on organizational justice. The conclusion isteam chracteristics, organizational justice, and work ethichave a direct effect on teacher job performance of state primary school at East Jakarta. There are suggestions that team characteristics, organizational fairness, and work ethics need to be improved in an effort to improve teacher performance.. Keywords: work ethic, team chracteristics, organizational justice, and, job performance